Tanggung Jawab Rumah Sakit Terhadap Kejadian Malpraktik Yang Dilakukan Oleh Tenaga Kesehatan Kepada Pasien Menurut Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan - Hidayat, Nandang Fadhil Hidayat; Hidayat, Nandang Fadhil; Asyhadie, H. Zaeni (Private Law, 2024)
This research aims to determine the legal responsibility of hospitals to patients for medical malpractice committed by healthcare workers. This research is normative, utilizing a statutory and conceptual approach. The results of this research show that the hospital is fully responsible for all medical actions carried out by its healthcare workers. The hospital, as the manager of health services, is obligated to protect patients and hospital resources, as stipulated in Law Number 17 of 2023 on Health. Malpractice can occur due to several factors, such as lack of experience among healthcare workers, misdiagnosis, and negligence.